Anti-androgen vinclozolin impairs sperm quality and steroidogenesis in goldfish - Hatef, Azadeh; Alavi, Sayyed Mohammad Hadi; Milla, Sylvain; Křišťan, Jiří; Golshan, Mahdi; Fontaine, Pascal; Linhart, Otomar (Aquatic toxicology (Amsterdam, Netherlands), 2012)
In mammals, vinclozolin (VZ) is known as anti-androgen, which causes male infertility via androgen receptor (AR) antagonism. In aquatic animals, the VZ effects on reproductive functions are largely unknown and results are somewhat contradictory. To understand VZ adverse effects on male reproduction, mature goldfish (Carassius auratus) were exposed to three nominal VZ concentrations (100, 400, and 800 μg/L) and alternations in gonadosomatic (GSI) and hepatosomatic indices (HSI), 17β-estradiol (E(2)), 11-ketotestosterone (11-KT) and sperm quality were investigated compared to the solvent control. One group was exposed to E(2) (nominal concentration of 5 μg/L), an estrogenic compound, as a negative control. Following one month exposure, GSI and HSI were unchanged in all VZ treated groups compared to solvent control. Sperm volume, motility and velocity were reduced in fish exposed to 800 μg/L VZ. This was associated with the decrease in 11-KT level, suggesting direct VZ effects on testicular androgenesis and sperm functions. In goldfish exposed to 100 μg/L VZ, 11-KT was increased but E(2) remained unchanged. This is, probably, the main reason for unchanged sperm quality at 100 μg/L VZ. In goldfish exposed to E(2), GSI and 11-KT were decreased, E(2) was increased and no sperm was produced. The present study shows different dose-dependent VZ effects, which lead to impairment in sperm quality via disruption in steroidogenesis. In addition to VZ effects through competitive binding to AR, our data suggests potential effects of VZ by direct inhibition of 11-KT biosynthesis in fish as well as abnormalities in sperm morphology.
Keywords: Oxazoles; zvířata; oxazoly; Spermatozoa; testis; Animals; testosteron; karas zlatý; antagonisté androgenů; estradiol; spermie; chemické látky znečišťující vodu; Testosterone; Androgen Antagonists; Male; mužské pohlaví; Estradiol; Goldfish; Water Pollutants, Chemical; Testis